Identification and diversity of Y-chromosome haplotypes in Qinghai yak populations - Ma, Z.J.; Xia, X.T.; Chen, S.M.; Zhao, X.C.; Zeng, L.L.; Xie, Y.L.; Chao, S.Y.; Xu, J.T.; Sun, Y.G.; Li, R.Z.; Guanque, Z.X.; Han Jianlin; et al. (Wiley, 2018)
The aim of the present study was to perform a preliminary analysis of the characterization and diversity of Y‐chromosome haplotypes/haplogroups in yak of Qinghai Province, China. A total of 322 male yaks from nine populations belonging to three officially recognized breeds (Gaoyuan, Huanhu and Datong) were sampled. Animals were genotyped using six previously reported Y‐SNPs present in the SRY, USP9Y, UTY, AMELY and OFD1Y genes and four new Y‐SNPs in the OFD1Y gene (g.569A>C, g.578A>C, g.608G>T and g.653G>C) identified in this study. Seven Y‐chromosome haplotypes (H1–H7) were identified according to the combination of the 10 Y‐SNPs. H1, H2 and H6 were the most common and shared haplotypes across all yak populations/breeds. Private haplotypes H3 and H7 were detected in the Datong breed; H4 in Guoleimude, Qumalai, Qilian, Tianjun and Ganglong populations; and H5 in Qumalai of Gaoyuan breed. Haplotype clustering and network analyses inferred two haplogroups, Y1 and Y2, indicating two divergent lineages of paternal origins of Qinghai yak. The analysis of molecular variance showed a significant difference among individuals (P < 0.0001) with more than 93% of the total genetic variation present within populations, suggesting a weak genetic structure among Qinghai yak populations. The overall Y‐haplotype diversity was 0.538 ± 0.028, showing a relatively high diversity in Qinghai yak. The Gaoyuan and Datong breeds had similar haplotype diversities (0.547 ± 0.030 and 0.553 ± 0.083, respectively), which were higher than that of the Huanhu breed (0.441 ± 0.098). Our results support the conservation and sustainable use of unique yak genetic resources in Qinghai.